2019
DOI: 10.5539/elt.v12n6p161
|View full text |Cite
|
Sign up to set email alerts
|

A Corpus Tools-assisted Evaluation of Three ESP Textbooks in China

Abstract: ESP textbook plays an important role in facilitating students to develop their profession-related language skills. However, ESP textbooks published in China are less developed and often criticized as ignoring the training of language skills. This research aims to reveal the specific problems of China’s ESP textbooks by conducting a multiple-case study. Three ESP textbooks used by ESP courses participants from G University in China were selected: “Computer Professional English Course&rdq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Complementary evidence from the procedural taxonomy and opposing user responses to the unit structure suggested that since it takes time, effort and money to write varied and creative activities for presenting and practising language engagingly, CPD chose to employ the same type and number of activities in look-alike units, and thus self-inflicted the same inflexibility, for which many ESP materials have frequently been stigmatised as "assembly-line" productions (Ferguson, 2013;Gomez-Rodriguez, 2010;Hutchinson & Waters, 2010, p. 107;Mountford, 1988;Pilbeam, 1987). For this reason, like others in the past, wanting a change from their fixed, reading-and word-focused ESP course, the present participants too required more involvement in small-group fun oral-fluency activities rather than "reproductive language work" (Celik, 2018;Nunan, 2004, p. 32;Ou, 2019;Razmjoo & Raissi, 2010;Wang, 2010). In addition to more room for creativity in their communicative outputs, Turkish DS, being no different from other lower-level EFL learners, using global English materials, demanded bilingual support, grammar reference and extra language practice for three main reasons: i. L1 equivalents facilitated vocabularybuilding and enabled cross-lingual/cultural comparisons, ii.…”
Section: Importance Of Harmonising Diverse Learning Foci Modes and Pr...mentioning
confidence: 72%
See 1 more Smart Citation
“…Complementary evidence from the procedural taxonomy and opposing user responses to the unit structure suggested that since it takes time, effort and money to write varied and creative activities for presenting and practising language engagingly, CPD chose to employ the same type and number of activities in look-alike units, and thus self-inflicted the same inflexibility, for which many ESP materials have frequently been stigmatised as "assembly-line" productions (Ferguson, 2013;Gomez-Rodriguez, 2010;Hutchinson & Waters, 2010, p. 107;Mountford, 1988;Pilbeam, 1987). For this reason, like others in the past, wanting a change from their fixed, reading-and word-focused ESP course, the present participants too required more involvement in small-group fun oral-fluency activities rather than "reproductive language work" (Celik, 2018;Nunan, 2004, p. 32;Ou, 2019;Razmjoo & Raissi, 2010;Wang, 2010). In addition to more room for creativity in their communicative outputs, Turkish DS, being no different from other lower-level EFL learners, using global English materials, demanded bilingual support, grammar reference and extra language practice for three main reasons: i. L1 equivalents facilitated vocabularybuilding and enabled cross-lingual/cultural comparisons, ii.…”
Section: Importance Of Harmonising Diverse Learning Foci Modes and Pr...mentioning
confidence: 72%
“…It was also worth noting that corpus evidence was seldom employed to corroborate findings from expert and user reviews; for instance, frequency counts of technical words were performed to crosscheck appropriateness of lexical content in Darani's (2014) comparison of local andglobal ESP materials andBoshrabadi et al's (2015) investigation of teacher/student-perceived lexical needs and coursebook realisations, whereas Ou (2019) alone used corpus tools to determine the extent of subject coverage, variety of discourse markers, amount of vocabulary recycling and text difficulty levels across Chinese-made series. Scantiness of corpus information, coupled with overuse of generic checklists/schemes, may however have led to duplicative results on coursebook efficiency because global materials often achieved user satisfaction in almost all aspects except for provision of L1support and culturally-responsive teaching (e.g.…”
Section: Trends and Gaps In Esp Coursebook Researchmentioning
confidence: 99%
“…e non-quantitative evaluation discussed in this paper does not take objective teaching evaluation as the evaluation index, but uses effective evaluation means to make a qualitative analysis of English classroom teaching, timely feedback evaluation teaching, and evaluation, which depends on the realization of teaching and the learning evaluation system, including quantitative and qualitative evaluation indexes, so as to motivate students who often participate in English learning. It also provides teaching reference for English teachers in Classroom Teaching [12][13][14][15].…”
Section: Teaching Evaluationmentioning
confidence: 99%